Classification of cysts with follicular germinative differentiation. (12th October 2015) - López‐Takegami, Juan C. H.; Wolter, Manfred; Löser, Christoph; Maiweg, Corinna; Jones, Meriem; Metze, Dieter; Böer‐Auer, Almut
Abstract : Background: Cysts are very common in the routine of dermatopathology but follicular germinative (trichoblastic) differentiation in cysts is seen rarely. The presence of follicular germinative differentiation in a cyst alerts to consider the possibility of a basal cell carcinoma (BCC) arising in a cyst. Methods: Five cystic lesions with zones of follicular germinative differentiation were collected. Hematoxylin and eosin sections were reassessed for architecture, types of follicular differentiation and stromal characteristics; immunohistochemical studies with Ber‐EP4 were analyzed. Articles about follicular germinative differentiation in cystic lesions were reviewed. Results: Cystic lesions with follicular germinative differentiation have been described in the literature under various names including trichoblastic infundibular cyst, cystic trichoblastoma, cystic panfolliculoma (CPF), dermoid cyst with basaloid proliferations, folliculosebaceous cystic hamartoma and BCC occurring in infundibular cysts. The lesions presented by us could be classified as three cystic trichoblastomas, one CPF and one cystic hamartoma with follicular germinative differentiation. Conclusions: Histopathologically, cystic trichoblastomas can be separated from CPFs. Some lesions defy classification and may be regarded as cystic follicular hamartomas. The presence of follicular papillae and bulb‐like structures, advanced follicular differentiation like that of inner and outer root sheath exclude the differential diagnosis of BCC arising in a cyst.